INTERPRETASI MAHKAMAH AGUNG TERHADAP ALASAN PEMBATALAN PUTUSAN ARBITRASE DALAM PASAL 70 UU NO. 30/1999 - Ilhami Ginang Pratidina (Universitas Airlangga, 2014)
Article 70 of Law No. 30 of 1999 on Arbitration and Alternative Dispute Resolution (Law No. 30/1999) establish three basic reasons limitedly as cancellation of the arbitration decision. In the case of PT.Comarindo Express Tama Tour against Yemen Airways, the Supreme Court considers the court decision based on the elucidation and cancels the arbitration award on the grounds out of Article 70 of Law No. 30/1999. This paper seeks to elaborate on the interpretation of the Supreme Court against the cancellation reason arbitration award in terms of universal principles in the practice of modern arbitration and the legislation laws to use the statute approach, conceptual approach and case approach and suggests some court decision both Indonesian court and foreign court. The Supreme Court in this case misapplied the law due to the fact that consideration of the elucidation is in contrast to the universal principles in the practice of arbitration.Keywords: arbitration, the reason for the cancellation decision.